2004
DOI: 10.1007/s00268-003-7323-y
|View full text |Cite
|
Sign up to set email alerts
|

Fishing Line Suture: Cost‐saving Alternative for Atraumatic Intracutaneous Skin Closure—Randomized Clinical Trial in Rwanda

Abstract: Experience with the use of nylon fishing line for surgical sutures has been reported from several African countries. A recent publication suggested that fishing line and an injection needle may provide an atraumatic suture that is especially suitable for intracutaneous skin closures. This article provides further empirical support for such alternative technology. We describe a randomized, blinded clinical trial conducted in Butare (Rwanda) with 220 cutaneous wounds closed by intracutaneous sutures, with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In poor countries where commercial thread is not available, surgeons use sterilized Nylon fishing line bought at the local market. [3][4][5][6] Nevertheless, despite extensive clinical experience with Nylon sutures, there are few publications about the use of Nylon meshes in hernia repair. Nylon implants have mostly been used for closure of laparostomies or darn.…”
mentioning
confidence: 99%
“…In poor countries where commercial thread is not available, surgeons use sterilized Nylon fishing line bought at the local market. [3][4][5][6] Nevertheless, despite extensive clinical experience with Nylon sutures, there are few publications about the use of Nylon meshes in hernia repair. Nylon implants have mostly been used for closure of laparostomies or darn.…”
mentioning
confidence: 99%
“…It is used for several types of sutures. A sterilised polyethylene fishing line from the local market is used by surgeons in some low-middle income countries (LMIC) where the commercial surgical thread is not readily available [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Freudenberg S et al [7] They concluded from their study that homemade sutures should be recommended to surgeons in countries where the cost of surgical materials often remains an obstacle to life-saving operations.…”
Section: Study Inferencementioning
confidence: 99%
“…In the early days of mesh implantation nylon meshes were used, but later replaced by stronger materials with less chronic inflammation. Nylon fishing line has recently been recommended for skin closure [19,20] .…”
Section: Discussionmentioning
confidence: 99%